O jogo simbólico livre e dirigido e as manifestações do juízo moral em crianças da educação infantil - Batista, Drielly Adrean [UNESP] (2014)
The development of moral judgment is an continuous, interactive and dynamic process that begins when the child is born and lasts for life, with different characteristics in each period of the development life cycle. This development mainly depends on the interaction of the individual with the means and devices provided by different social moral experiences. Thus, it should begin to be worked from an early age, by socializing groups, such as school, family and community , aimed at building autonomy . In this perspective , the purpose of this research was to analyze and compare manifestations of moral judgment in the free symbolic play and directed at children from kindergarten, aged four and five years. The main theoretical contribution of the research were the epistemologist Jean Piaget on the development of moral judgment in children, as well as in later empirical studies on the topic. The methodology was qualitative, through multiple case study, whose main instrument for data collection observation of children in times of free and directed symbolic play. The results showed that among the manifestations of moral judgment that arise during the free games are symbolic and directed fairness, cooperation, respect the rules and lie / whistleblower. It was possible to verify that educators are few interventions during times of games and that children tend to repeat stereotypical behaviors of educators when they assume the role of teachers. The analyzes showed that free symbolic games and / or facilitators may be directed to the pedagogical work that seeks the integral development of children and that the intervention of the educator is required to assist in the construction of children's morality